Next stop - Fong, Debbie (New York : RH Graphic, an imprint of Random House Children's Books, 2024)
Still grieving her brother's death, Pia, a soft-spoken middle-schooler, embarks on a bus tour that changes her life.
3-6
GN400L
Keywords: Grief -- Comic books, strips, etc; Grief -- Juvenile fiction; Bus travel -- Comic books, strips, etc; Bus travel -- Juvenile fiction; Voyages and travels -- Comic books, strips, etc; Voyages and travels -- Juvenile fiction; Middle school students -- Comic books, strips, etc; Middle school students -- Juvenile fiction; Grief -- Fiction; Bus travel -- Fiction; Voyages and travels -- Fiction; Middle school students -- Fiction; Road trip comics; Graphic novels; Comics (Graphic works)